Effect of different concentration of Benzyl Amino Purine and Kinetin hormones on micro propagation of aerobic rice / Natasha Nabila Nordin - Nordin, Natasha Nabila (Faculty of Plantation and Agrotechnology, 2015)
The study is to generate shoot from the direct seedling of MRIA I and to determine the effectiveness of combination of MS media vitamin with Benzyl Amino Purine (BAP) and Kinetin (Kn) on MRIA l.treatment that has been used were 0.0mg/L BAP and Kn, 0.25mg/L BAP and 0.50mg/L Kn, 0.50mg/L BAP with 0.25mg/L Kn , 0.50mg/L BAP with 0.50mg/L Kn , 0.75mg/L BAP with 1.00mg/L Kn, 1.00mg/L BAP with 0.75mg/L Kn and 1.00mg/L BAP with 1.00mg/L Kinetin. In the present study, the combination of MS media vitamin with 0.50mg/L of BAP and 0.50mg/L of Kinetin is a best combination in proliferation and multiplication and length of shoot in aerobic rice. The best combination in determine the width of shoots respectively was MS media vitamin with 1.00mg/L of BAP and 1.00mg/L of Kinetin.